Enhanced Heterogeneous Fenton Degradation of Organic Pollutants by CRC/Fe3O4 Catalyst at Neutral pH - Wang, Chuan; Jiang, Rui; Yang, Jingxin; Wang, Pingshan (Frontiers in Chemistry, 2022)
Fe3O4-based heterogeneous Fenton catalysts have been widely employed for degrading organic pollutants, however it is challenging to use them in highly efficient and recyclable application in wastewater treatment. In this work, carboxylate-rich carbon (CRC)-modified Fe3O4 magnetic particles are prepared by the sol-gel self-combustion method, where CRC is obtained from the carbonization of sodium gluconate. The CRC/Fe3O4 catalyst exhibits high heterogeneous Fenton degradation performance. The complete 10 mg L−1 methylene blue (MB) removal is achieved in 180 min under conditions of 10 mM H2O2 and 1.00 g of L−1 CRC/Fe3O4 at neutral pH. After five cycles, the structure and morphology of CRC/Fe3O4 composites remained unchanged and the catalytic activity also remained unaltered. Moreover, phenol, benzoic acid (BA), sulfamethazine (SMT), and tetracycline (TC) were also degraded in the heterogeneous Fenton reaction using CRC/Fe3O4 as a catalyst. The strong coordinating ability of –COOH/ –COO– functionalities of CRC formed strong bonds with Fe(II/III) ions on the surfaces of Fe3O4 particles, which was conducive to adsorption of organic matter on the surface of the catalyst and promoted the occurrence of heterogeneous Fenton reactions. It was found that CRC/Fe3O4 had higher removal rates for the adsorptive exclusions of pollutants, such as TC and MB, whereas there were lower removal rates for phenol, BA, and SMT. This work brings potential insights for development of a novel adsorption-enhanced heterogeneous Fenton reaction for wastewater treatment.